Menembus Batas Geografis: Tantangan dan Harapan Pemerataan Infrastruktur Pendidikan di Pedalaman Papua - Sukmameti Sukmameti; Hidayat Hidayat (Lembaga Publikasi Ilmiah Nusantara, 2026)
The equalization of educational infrastructure in the interior of Papua still faces complex challenges caused by geographical barriers and limited accessibility. This community service activity aims to map the main obstacles while formulating tactical strategies to accelerate the development of educational facilities in underdeveloped, frontier, and outermost (3T) regions. The method used in this program consisted of participatory assistance and field observations across several remote district points. The evaluation results indicate that the primary challenges include high material logistics costs, a shortage of resident educational personnel, and extreme topographical conditions that hinder the distribution of information technology facilities. However, collaboration among local governments, customary leaders, and local communities has raised new hopes through a self-reliance-based development model and the utilization of local materials that are adaptive to the environment. This activity successfully formulated policy recommendations regarding boarding-school models and the integration of renewable energy to support teaching and learning activities. In conclusion, breaking through Papua's geographical boundaries requires not only physical development but also a socio-cultural approach that positions local communities as subjects of development. The hope for educational equity in the future depends on the consistency of infrastructure policies integrated with the strengthening of local human resources to realize social justice for all Papuan people.